2019
DOI: 10.1021/acsabm.9b00012
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Povidone-Iodine-Conjugated Cross-Linked Polystyrene Resin for Water Bacterial Decontamination

Abstract: Bacterial contamination in water purification systems is generating significant concern as a global health issue. In this paper, we describe fabricating antibacterial povidone-iodine-conjugated cross-linked polystyrene resins (i.e., P­(St-DVB-NVP)-I2) and investigating them as antimicrobial agents for water decontamination. Comprehensive antibacterial tests showed that the addition of povidone-iodine to polystyrene resins resulted in strong antibacterial activity against pathogenic bacteria. In addition, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Bacteria, as one of the main pathogenic microorganisms that induce infection, can induce a variety of diseases, , such as tuberculosis, scarlet fever, sepsis, and other inflammations . These diseases are self-limiting, difficult to treat, and even highly fatal, which seriously threatens human life and health.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria, as one of the main pathogenic microorganisms that induce infection, can induce a variety of diseases, , such as tuberculosis, scarlet fever, sepsis, and other inflammations . These diseases are self-limiting, difficult to treat, and even highly fatal, which seriously threatens human life and health.…”
Section: Introductionmentioning
confidence: 99%
“…PVP is a water-soluble, hydrophilic polymer, and substantial incorporation of said PVP product into a water-insoluble polymer matrix will have significant effects on the resultant product properties. One previous publication showed that the conjugation of PVP-I with cross-linked polystyrene resin could be used for bacterial decontamination of water, but in such cases, the PVP-I serves as a functional polymer rather than part of the fundamental engineering plastic matrix ( 14 ). There are also publications and reported research activities on the generation of water-insoluble polymer-iodine complexes in which the iodine is complexed with the matrix polymer via iodine solutions or vapor deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Development of efficient disinfection techniques and targeted therapeutics towards pathogenic microorganisms is one of the key focus areas in research [6,7]. One of the approaches is reinventing the use of potent antimicrobial inorganics such as copper [8], iodine [9], zinc [10], and silver [11] since they are abundantly present in nature and can achieve disinfection of pathogenic microbes in an environment friendly manner.…”
Section: Introductionmentioning
confidence: 99%